Sharing economy: A review and agenda for future research. (August 2016) - Cheng, Mingming
Highlights: Sharing economy has a strong intellectual tradition from five research streams. Sharing economy literature lacks multi-level theoretical perspectives. It is unclear how sharing economy redefines the roles of consumers. The paper highlights opportunities offered by a visual analytics approach. Abstract: This paper provides an objective, systematic and holistic review of the sharing economy (SE) academic literature to uncover the theoretical foundations and key themes underlying the field by using co-citation analysis and content analysis. Sixty-six publications on sharing economy with ten papers related to tourism and hospitality from 2010 to 2015 (inclusive) have been identified. This paper revealed three broad areas of foci with sharing economy research in general: (1) SE's business models and its impacts, (2) nature of SE, and (3) SE's sustainability development as well as two areas of foci in tourism and hospitality specifically: (1) SE's impacts on destinations and tourism services (2) SE's impacts on tourists. The sharing economy has a strong intellectual tradition from lifestyle and social movement field, consumption practice and sharing paradigm. This paper presents a more robust framework and holistic understanding of the sharing economy field and calls for a new theory-informed research agenda on sharing economy to coalesce multi-level perspectives.